EFL Students’ Anxiety in Oral Presentation in Thesis Examination during Covid- 19 Pandemic Era: Factors and Strategies - Sahril Nur; Geminastiti Sakkir; Rosmini (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This research discusses EFL students’ anxiety in oral presentation in thesis examinations. This research aims to reveal the factors causing students’ anxiety and the strategy that EFL students apply to overcome/reducing their anxiety. The researchers conducted this research in Islamic Higher Education and this research used a qualitative method with a case study approach. The participants of this research were 7 (seven) EFL students that the data were analyzed using thematic analysis based on Braun and Clarke (2016). Then, the researchers used Wilson’s (2004) model semi-structured interview that the researchers arranged as the research instruments. The results revealed that the factors causing students’ anxiety generally: linguistic factors and non-linguistic factors (psychology factors, environment factors, and individual factors). Furthermore, the researchers found that EFL students apply strategies to overcome anxiety in oral presentation: preparation, relaxation, positive thinking, peer seeking, self-entertaining, and praying. Therefore, the lecturers have to know their students’ anxiety in oral presentation and they have to apply the best strategy in teaching English as Foreign Language.